ANALISIS KEMAMPUAN MEMBACA PEMAHAMAN TEKS NARASI PADA SISWA KELAS IV SEKOLAH DASAR - Rostia Sabaniah, Nevi; Nuriyanti, Risma; Sulaiman, Zoni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the reading comprehension ability of fourth-grade elementary school students in understanding narrative texts. The aspects of reading comprehension investigated include identifying the main idea, understanding the plot of the story, drawing conclusions, determining the moral value or message of the story, and understanding the meaning of words or terms in the text. This study employed a qualitative descriptive approach. The participants were fourth-grade students selected as the research subjects. Data were collected through essay tests, interviews, and documentation. The research instruments consisted of essay test questions developed based on reading comprehension indicators and a scoring rubric used to assess students’ responses. Data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that students’ reading comprehension ability was generally in the good category. Most students were able to identify the main idea, understand the plot, draw conclusions, determine the moral values or messages, and understand the meaning of words in narrative texts. However, some students still experienced difficulties in drawing conclusions and understanding certain words found in the reading passages. Therefore, students’ reading comprehension skills need to be continuously improved through more active and varied learning activities.